Anticipating Losses as a Result of the Use of Special Purpose Vehicles in the Perspective of Indonesian National Law - Widya Agustina Siregar (Interdisciplinary Social Studies, 2025)
This research has been done in regards on several problems relating to the utilization of Special Purpose Vehicle (SPV) in business transaction, particularly in the businesses involving an Indonesian company or Indonesian entity. According to the research which has been done there are three major problems becoming the object of the research : firstly how far is the legality of the SPV utilizationin in the business from Indonesian law perspective, secondly how the practice of the SPV utilization from the perspective of business law in general, thirdly how to make the concept of SPV as a law smuggling shall not creating the loss to the certain party particularly the country of the Republic of Indonesia. The method used in this research is normative law research through the approach of cases, rules and regulations, comparative, and conceptual. The normative law research is based on the implementation of the rule of law concept in order to create a well-controlled and well-organized country. The cases approach has been done by evaluating the cases relating the SPV as a law smuggling and the opportunity to anticipate the loss of the country arising from the use of SPV as a law smuggling. The regulations and comparative approach has been done by evaluating the rules and regulations as currently exist in Indonesia and to make a comparative study with other countries in order to obtain a guidance to establish a regulation regarding the limitations of the SPV utilization in Indonesia. The theoretical and conceptual approach has been used to analyse the problems arising from the utilization of SPV.